Air Travel as Part of the Tourism Experience: Antecedents of Travel Advocacy Among Airline Passengers - Marceilla Suryana (Journal of Consumer Studies and Applied Marketing, 2026)
Air travel has increasingly evolved from a purely functional mode of transportation into an integral component of the tourism experience. Despite this transformation, airline research continues to emphasize service quality, satisfaction, and loyalty, while paying limited attention to the mechanisms by which travel experiences translate into advocacy behavior. This study investigates the influence of airline service quality and digital service experience on travel advocacy, with customer experience, perceived value, and memorable travel experience as mediating factors. A quantitative cross-sectional survey was conducted among 500 airline passengers in Indonesia who had undertaken leisure travel by air within the previous twelve months. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that both airline service quality and digital service experience significantly enhance customer experience. Customer experience subsequently positively affects perceived value and memorable travel experience, thereby serving as a key mechanism linking airline experiences with advocacy behavior. In turn, perceived value and memorable travel experience significantly influence travel advocacy, with the latter emerging as the strongest predictor. The results highlight the central role of customer experience in transforming service encounters into advocacy behavior. The study extends airline and tourism literature by moving beyond the conventional service quality–satisfaction–loyalty paradigm and positioning travel advocacy as the ultimate behavioral outcome. The findings further suggest that airlines should focus on creating seamless, meaningful, and memorable travel experiences across both physical and digital touchpoints to encourage positive recommendations and advocacy.